ARCHAEOLOGICAL RESEARCH TACARACA, A ICA SITE OF SOUTH COAST PERU - Mallco Huarcaya, Rafael (2015)
This article aims to document and understand the development of Ica culture and subsequent occupation of the Archaeological site Tacaraca, to encourage such research and cultural appreciation. As is known, the area of Ica was the scene of two major development of Paracas and Nasca cultures (800 a.C. to 600 d.C.), however, during the Late Intermediate Period (1000 -1470 d.C), after the Huari decline, Ica culture was the most important company that was established in the Ica valley and had as Tacaraca main center. The main buildings identified in the place match constructions administrative and religious well- planned structures that are interconnected by walkways and stairs leading to important architectural spaces with fine finishes.